A scoping review of assessment tools and factors influencing spoken language development among pediatric cochlear implant users - Deepashini Harithasan; Cila Umat (Penerbit Universiti Kebangsaan Malaysia, 2022)
The spoken language development strongly depends on the normally functioning auditory system. For children with severe or profound hearing loss, cochlear implant has become the best solution in improving and promoting spoken language, quality of life, self-esteem and social well-being. Standardized self-report questionnaires are considered as the most widely used and low-cost approach to measure spoken language development among children. We aimed to provide an overview of the questionnaires available for assessing the spoken language development among children with cochlear implant. In addition, factors that may influence the development of good spoken language were also reviewed. A literature search from January 2010 to December 2020 making use of the Science Direct and PubMed databases was conducted. Medical Subject Headings (MeSH) and other key words for the search were (communication OR language) AND cochlear implant AND (children OR pediatric) AND (questionnaire OR survey). Research articles that were identified in the database using the keywords were refined by year. Only original articles were selected. Articles that quoted all the selected key words in the title and abstract; and written in English with full text were included in the review. Twelve instruments were utilized in the methodology of the 10 articles. Only one instrument was specific for spoken language assessment of children with cochlear implant. The age at which a child received an implant, good rehabilitation program and active involvement of parents was found to influence development of good spoken language skills among the cochlear implanted children. Cochlear implants provide deaf children with the opportunity to develop spoken language skills. Longer use of a cochlear implant dramatically affects the amount of spoken language. Rather, it was cochlear implantation at a younger age that served to assists spoken language competence.